Advanced immunology in aging population: unveiling the complexities of vaccine responsiveness - Han, Yan; Huang, Yanhao; Zhou, Yuanyu; He, Wanke; Luo, Gaomei; Yang, Liu; Chen, Yanbin; Zhu, Yiqi; Jiang, Wei; Xiao, Chanchan; Yan, Jianhui (Frontiers in Aging, 2025)
With the accelerating global population aging, vaccine responsiveness in older adults has emerged as an increasingly critical issue. This review systematically explores age-related changes in immune system function and their impacts on vaccine efficacy. Firstly, we outline the characteristics of immunosenescence and its regulatory effects on vaccine effectiveness from three perspectives: cellular, molecular, and signaling pathway levels. Secondly, we summarize methods for predicting vaccine immune responsiveness (such as biomarkers and advanced immunological assays) and current mainstream strategies for enhancing vaccine immune responsiveness, while enumerating several prominent novel vaccine formulations targeting the older adult population. Finally, we discuss existing controversies and future research directions regarding the study of vaccine responsiveness in older adults, and comprehensively evaluate the current research status of vaccine responsiveness in this demographic. By synthesizing extensive evidence, this review aims to provide new insights into addressing the challenges of vaccinating the older adult population and lay a theoretical foundation for developing more effective immunization strategies tailored to this vulnerable group.